Epiphytic and endophytic bacteria that promote growth of ethnomedicinal plants in the subtropical forests of Meghalaya, India - War Nongkhla, Fenella Mary (Universidad de Costa Rica, 2014)
The present study was aimed to investigate the endophytic and epiphytic bacteria associated with selected ethnomedicinal plants from the pristine subtropical forests of Meghalaya and analyse them for plant growth promotion and antagonistic ability. This study is an attempt to explore plant associated bacteria which are beneficial to host plants, and thus aid in the conservation of ethnomedicinal plants of the studied subtropical forests, which are dwindling due to exploitation. The plant growth promotion parameters like indole acetic acid (IAA) production, mineral phosphate solubilisation, acid phosphatase activity, presence of 1-aminocyclopropane-1-carboxylic acid deaminase (ACC) gene, nitrogen fixation, cellulose digestion, chitin and pectin were screened among the isolates. The study revealed significant differences in bacterial population not only between the epiphytic and endophytic microhabitats, but also amongst the host plants. Out of the 70 isolated plant associated bacteria, Bacillus sp., Serratia sp., Pseudomonas sp., Pantoea sp., and Lysinibacillus sp. showed potent plant growth promotion properties. Bacillus siamensis C53 and B. subtilis cenB showed significant antagonistic activity against the tested pathogens. This study indicated the isolates inhabiting the plants prevalent in the subtropical sacred forests that could be explored for use as plant growth promoters while practising the cultivation and conservation of ethnomedicinal plants.